Banking Health Assessment of Commercial Banks in Indonesia Using RGEC Methods: A Comparative Study - Wiwiek Mardawiyah Daryanto; Agung Sri Utami; Tri Septia Rakhmawati (Sekolah Tinggi Manajemen IPMI, 2019)
The study aims to analyze and compare the banking health assessment of commercial banks in Indonesia using RGEC methods. RGEC methods are included Risk Proile, Good Corporate Governance, Earnings, and Capital (RGEC). This study used descriptive with quantitative approach. The variables in this study includes Risk Proile using ratio of Non-Performing Loans (NPL) and Loan to Deposit Ratio (LDR), Good Corporate Governance (GCG) using Composite Rating GCG, Earnings using ratios of Return on Assets (ROA), Net Interest Margin (NIM), and Capital using Capital Adequacy Ratio (CAR). The data were collected from audited inancial report of two commercial banks in Indonesia which are PTBank UOB Indonesia and PTBank KEB Hana Indonesia for the period 2013 to 2017. The result showed that the inancial health level of PT Bank UOB Indonesia and PT Bank KEB Hana Indonesia was quite healthy. It indicates that the ability of the corporate's performance results had achieved very well.